A Educação de pessoas Jovens, Adultas e Idosas/EJAI: possibilidades de outras pedagogias - VIEIRA, Myrhia Sâmila Santos (2023)
The research aims to understand the subjects inserted in the Education of Young, Adult and Elderly People - EJAI, as well as the reasons for not having accessed School Education before. In addition, the work aims to reflect on the possibility of Other Emancipating Pedagogies, based on Freire and Arroyo. The investigation has a qualitative approach, carried out through bibliographical and field research, with insertion of relevant data from the Teaching Internship at EJAI. The techniques used for data production were non-directive interviews, life history and observation. The main authors who guided the discussion were Arroyo (2014), Freire (2018), Freire (2019), Jardilino and Araújo (2014) and others. As a result of the research, we conclude that the subjects of EJAI are people who face educational, social, cultural, economic barriers, dealing with relationships of denial of rights, subordination and oppression. In addition, with regard to pedagogical work, we identified that it needs to be at the service of the students' human and educational training processes. Therefore, we conclude the need for Other pedagogies with an emancipatory conception, in which the subjects, who had their rights denied, are valued in their life stories, their knowledge, their actions, as citizens, subjects of law in the contextualized teaching-learning processes, resignified, aiming at equal access to education as a social good, guarantee of human rights.